Exploring the approaches to care of faith-based and secular NGOs in Cambodia that serve victims of trafficking, exploitation, and those involved in sex work. Issue 5 (13th June 2017) - Frame, John
Abstract : Purpose: Faith-based organisations (FBOs) and secular NGOs provide important services to victims of trafficking, exploitation, and those involved in sex work, yet comparative analysis of their approaches to care has lacked attention in the literature. The purpose of this paper is to examine these two types of organisations, exploring the extent to which faith influences the ways FBOs work with their clients. Design/methodology/approach: In total, 41 interviews were conducted with leaders of 13 Christian FBOs and 12 secular NGOs in Cambodia, and organisational mission statements were reviewed. An input-output conceptual model was used as a framework to gather and analyse data. Findings: While all FBOs maintained a high regard for their clients' spiritual needs and operated with a faith-related approach to care, secular NGOs also, at times, included culturally embedded religious elements into their programming. The nature of FBOs' faith-related programming, however, clearly distinguished these organisations from their secular counterparts. Despite such distinctions, similarities were maintained among both types of organisations in the behavioural or recovery outcomes they sought in their clients. Research limitations/implications: Limitations include the study's focus on organisations that serve a specific clientele in one development context. Research implications include the study pointing to the necessity of acknowledging the development context as critical to the ways in which religion may or may not influence the approaches to care of both FBOs and secular NGOs. The paper also contributes insight into the relationship between the non-resource input of faith, and services provided by FBOs. Practical implications: Given that both types of organisations sought change in their clients, practitioners should ensure that their organisational approaches to care are conducive to the outcomes they seek. Though organisational policy may stipulate that clients are free to choose whether or not to participate in faith-related programming, FBOs should always ensure a care environment in which clients feel free not to participate in such programming. Originality/value: Though FBOs and secular NGOs sought many similar behavioural or recovery outcomes from their clients, the development context in which these organisations worked – unlike some other contexts – and the role of faith "infusing" FBOs, led to clear, observable differences in their approaches to care. The study highlights the importance of taking into account these factors when seeking to decipher differences that may or may not exist between faith-based and secular non-state social policy actors.